Impact of the Winding-on-Speed and the Consequent Machine Efficiency on Productivity and Quality of final yarn - Rashid, MS (Bangladesh Journal of Scientific and Industrial Research, 2012)
DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9595 BJSIR 2011; 46(4): 481-486